Granulomatous Myositis Showing Fluctuating "Leopard-Man" Sign: A Case Report on FDG PET/CT Imaging. (December 2019) - Koyama, Masamichi; Terauchi, Takashi; Koizumi, Mitsuru; Sugiura, Yoshiya
Abstract : Abstract: A 57-year-old woman with a history of uterine endometrial carcinoma underwent PET/CT examinations for initial staging and posttreatment survey. Multiple patchy accumulations were noted in the muscles, particularly in both thighs. These accumulations resolved spontaneously 6 months after the follow-up examination. However, 3.5 years after the surgery, the multiple patchy accumulations reappeared in the muscle of the upper and lower extremities showing an increase in signal intensity from previous examination. A biopsy of the right thigh revealed epithelioid cell granuloma without necrosis. We therefore consider that this case might be "idiopathic" granulomatous myositis.